Penyuluhan Kesehatan Teknik Relaksasi Napas Dalam Untuk Mengurangi Kecemasan Pada Pasien Asma di Tanjung Mulia Hilir - Yuni Shanti Ritonga; Satriani Hartalina Gultom; Norong Perangin-angin; Riska Wani Eka Putri; Defri Elias Simatupang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Bronchial asthma is a chronic inflammatory respiratory disease due to increased sensitivity of the airways to various stimuli. Bronchial asthma is not only a public health problem in developed countries, but also occurs in developing countries (WHO, 2016). Anxiety is a vague feeling of worry due to discomfort or fear accompanied by an autonomic response (the source is often unspecific or unknown to the individual), a feeling of worry caused by the anticipation of danger. Anxiety is a sign of increased alertness to impending danger and allows individuals to take action to face the threat (Doenges, 2015). The prevalence of anxiety disorders ranges from 6-7% of the general population (females are more prevalent than males) (Stuart, 2006). Lecturers and students from the Nursing and Nursing Study Program at Imelda University, Medan, chose to hold health education activities with the aim of helping as well as training both individuals and families regarding deep breathing exercises. This makes them aware and more diligent in practicing their breathing. The health education carried out in the courtyard of the sub-district office in Tanjung Mulia downstream began with holding talk activities and continued with outdoor counseling activities. This health education activity is of great interest to families in the community and it is hoped that it can be used as a lesson and make individuals and families more aware of the importance of deep breathing exercises to reduce anxiety in people with asthma.